Design of Safe and Quality Potato Chips Product Packaging Using Quality Function Deployment Method - Azwar Harahap; Muhammad Zakaria; Syukriah Syukriah; Meutia Fadilla (International Journal of Engineering, Science and Information Technology, 2023)
Packaging serves as a food storage system that protects food and goods from natural processes and facilitates ease of transportation. This study aimed to address the problems related to cassava chip packaging, such as inappropriate sizes and packages that are prone to breaking, by applying Quality Function Deployment (QFD) in designing packaging that meets food safety and quality. Through interviews with customers, the study confirmed the existence of packaging problems and the dissatisfaction expressed by customers regarding the product packaging. QFD was employed to determine consumer needs and desires for a product design that conforms to quality characteristics and technical requirements. The study also used a consumer assessment questionnaire to identify the most important product attributes and design requirements that meet consumer expectations. The study found that rectangular packaging shapes, bright colored primary packaging colors, polypropylene plastic packaging materials, the location of the logo on the packaging in the middle of the package square, four, light color, and an image of sweet potato chips on the logo are factors that influence product packaging design that meets food safety and quality. This study's findings can be useful for practitioners and researchers in designing packaging that meets consumer expectations, as well as for promoting food safety and quality.